2014
DOI: 10.2106/jbjs.m.00859
|View full text |Cite
|
Sign up to set email alerts
|

Acute Rejection of Knee Joint Articular Cartilage in a Rat Composite Tissue Allotransplantation Model

Abstract: Immunorejection of chondrocytes in transplanted cartilage has been thought to be unlikely, but our data reveal that chondrocytes can undergo apoptosis in allotransplantation. This apoptosis involves the caspase-3 cascade and indicates that chondrocytes may induce acute rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Allogeneic chondrocytes are more accessible, but cartilage produced by them in articular surface defects in rats was resorbed by infiltrating immune cells [ 50 , 51 ]. This acute rejection of newly formed allocartilage was not prevented even by the strong immunosuppressive agents cyclosporine A (CsA) and cladribine (2-chlorodeoxyadenosine) [ 52 ]. Allogeneic cartilage formed by chondrocytes transplanted into articular cartilage defects was infiltrated in its deep part, submerged in subchondral bone and bone marrow, while on the surface of the transplant facing the joint cavity infiltrating cells were absent [ 50 , 52 ].…”
Section: Immunogenic Properties Of Chondrocytes – Implications For Chmentioning
confidence: 99%
See 1 more Smart Citation
“…Allogeneic chondrocytes are more accessible, but cartilage produced by them in articular surface defects in rats was resorbed by infiltrating immune cells [ 50 , 51 ]. This acute rejection of newly formed allocartilage was not prevented even by the strong immunosuppressive agents cyclosporine A (CsA) and cladribine (2-chlorodeoxyadenosine) [ 52 ]. Allogeneic cartilage formed by chondrocytes transplanted into articular cartilage defects was infiltrated in its deep part, submerged in subchondral bone and bone marrow, while on the surface of the transplant facing the joint cavity infiltrating cells were absent [ 50 , 52 ].…”
Section: Immunogenic Properties Of Chondrocytes – Implications For Chmentioning
confidence: 99%
“…This acute rejection of newly formed allocartilage was not prevented even by the strong immunosuppressive agents cyclosporine A (CsA) and cladribine (2-chlorodeoxyadenosine) [ 52 ]. Allogeneic cartilage formed by chondrocytes transplanted into articular cartilage defects was infiltrated in its deep part, submerged in subchondral bone and bone marrow, while on the surface of the transplant facing the joint cavity infiltrating cells were absent [ 50 , 52 ]. This suggested that immunisation of recipients occurred via the contact of chondrocytes with bone marrow cells.…”
Section: Immunogenic Properties Of Chondrocytes – Implications For Chmentioning
confidence: 99%
“…22,24,29,30 Giannini et al 29 hypothesized that this may be due in part to underappreciated immunogenicity of the allografts, which has been supported by basic science reasearch. [31][32][33] Others have argued that the size of the allograft tissue and mechanical factors lead to failure. 30 Patellofemoral instability is a source of these patellar and trochlear lesions, and the treatment of patellofemoral instability continues to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a universal strategy needs to be established to overcome IRRs for allogenic cartilage regeneration in large animals and facilitate clinical translation of engineered cartilage. [ 11,12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a universal strategy needs to be established to overcome IRRs for allogenic cartilage regeneration in large animals and facilitate clinical translation of engineered cartilage. [11,12] Recently, a novel immunoisolation strategy using semipermeable membrane (SPM) materials has emerged as a feasible solution to protect allotransplanted cells and tissues, such as fibroblasts, mesenchymal stem cells, and islets, from immune attack by the host. [13,14] For variable tissue regeneration, it is essential to choose a proper SPM material for simultaneous efficient immunoisolation and stable tissue survival.…”
Section: Introductionmentioning
confidence: 99%